The Relationship between Stock Returns and Trading Hours: Evidence from Amman Stock Exchange - Kharabsheh, Buthiena; Hani Megdadi, Mahera; Abu-ulbeh, Waheeb (International Journal of Engineering and Technology, 2018)
This study investigates the relationship between stock returns and trading hours for 22 shares listed on Amman Stock Exchange (ASE). We analyze the hourly trading data for the period Dec.2005 to Dec.2006. The two trading hours in ASE were split into four periods; first half of the first hour (10:00-10:30), second half of the first hour (10:30-11:00), first half of the second hour (11:00-11:30), and second half of the second hour (11:30-12:00). Using the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model, our results reveal that the hourly trading time significantly affects stock returns. Â Â